HUBUNGAN REMUNERASI DENGAN KEPUASAN KERJA TERHADAP ETOS KERJA DI SUBDEN I DETASEMEN C PELOPOR BRIMOB SURAKARTA - Saputro, Dedi Hermawan (Universitas Sahid Surakarta, 2014)
Bureaucratic reform within the police has been implemented since 2002. Namely by imposing and implementing several changes and reforms in the field of Instrumental, fields of structural and cultural fields. Past policies before the reform may be in the eyes of members, the leadership knows only demanding change and performance improvement without any compensation. But this time it was clear they would be rewarded with either an increase in welfare benefits or salary increases and performance. The purpose of this study was to determine the relationship between remuneration and jobÂ satisfaction with the work ethic and the members of staff employees in the first sub-detachment Detachment C Pioneers Brimob Surakarta. Subjects in this study were members and staff employees in the first subdetachment Detachment C Brimob Surakarta Pioneers 40 people. Sampling studies using random sampling. UsingÂ questionnaire data collection tool (questionnaire). Methods ofdata analysis using product moment correlation technique. Based on the calculation ofthe product moment analysis technique remuneration relationship with work ethic correlation coefficient ( rxy ) at = 0.656 , p = 0.000 (p < 0.01 ) and the relationship of job satisfaction with work ethic values obtained correlation coefficient ( rxy ) of = 0.692, p = 0.000 ( p < 0.01 ). These results indicate there is a significant positive correlation between the remuneration of the work ethic and satisfaction with work ethic , therefore it can be interpreted that both job satisfaction and remuneration variable can be used as predictors (independent variables) to predict or measure the work ethic that has members and Detachment C sub-detachment staffÂ Pioneers Brimob Surakarta.